A Novel Variant c.847T>C in CTSK Gene Leading to Pycnodysostosis: A Case Report. Issue 12 (March 2019) - Kochar, Inder Pal Singh; Sethi, Aashish; Ahamad, Ayesha
Pycnodysostosis is a rare genetic disorder with a prevalence of 1.7 per million births; it usually presents with short stature, osteosclerosis, increased bone fragility, and acro-osteolysis of distal phalanges. There are less than 200 cases reported worldwide and very few from South-East Asia. We present a case of pycnodysostosis who presented with short stature, acro-osteolysis of distal phalanges, and on genetic testing revealing a variant c.847T>C, p.Y283H, in exon 7 of the CTSK in homozygous state: not reported till date to the best of our knowledge.